Pengaruh Budaya Organisasi, Kepemimpinan Situasional dan Pola Komunikasi terhadap Disiplin Kerja dan Kinerja Karyawan pada PT. Central Proteinaprima Tbk. - Brahmasari, Ida Ayu; Siregar, Peniel (Jurnal Aplikasi Manajemen, 2009)
Contribution of employees' performances to the overall performance of organization is very important as they are one of the determinant of the organizational success and competitiveness. A new challenge faced by an organization encourage the creation of a new way to do something to improve the organization performance continuously. Therefore, organization culture may be used as a means to adapt any external organization changes as well as to integrate the internal organization. Moreover, communication and the leaders' ability to influence, motivate, and enable others to contribute to the effectiveness and success of the organizations of which they are members, are very essential to the organization. The purpose of this research is to prove and analyze the influences of corporate culture, situational leadership and communication pattern on employees' disciplines and performances. The results proved that corporate culture, situational leadership and communication pattern have significant influences on employees' disciplines and performances.